Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of mangosteen (Garcinia mangostana Linn.) rind extract against Aggregatibacter actinomycetemcomitans - Hendiani, Ina; Susanto, Agus; Carolina, Dyah Nindita; Ibrahim, Rahmat; Balafif, Felisha Febriane (Universitas Padjadjaran, 2020)
Introduction: The main contents of mangosteen (Garcinia mangostana Linn.) is xanthone with antibacterial activity. Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) was a gram-negative, facultative anaerobic bacillus that causes periodontal diseases such as localised aggressive periodontitis (LAP). Mangosteen rind extract could inhibit the growth of Porphyromonas gingivalis and A. actinomycetemcomitans. This study was aimed to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of mangosteen rind extract against A. actinomycetemcomitans. Methods: This study was an experimental and in-vitro study of antimicrobial properties of mangosteen (Garcinia mangostana Linn.).The extract of mangosteen was made by the maceration method using 70% ethanol solvent. A. actinomycetemcomitans (ATCC 43718) obtained from Laboratorium of Microbiology Airlangga University Surabaya. This study used a microdilution method and analysed using the Enzyme Linked Immune Sorbent Assay (ELISA). The determination of the MIC was measured using the formula for cell inhibition percentage. Three concentrations higher than the MIC standard were cultured on the Mueller Hinton agar. The lowest concentration on agar which was not found any growth of the bacterial colonies was determined as the MBC. Results: The results of this study indicated that the MIC and MBC of mangosteen rind extract against A. actinomycetemcomitans were 195.3 ppm and 1562.5 ppm, respectively. Conclusion: Mangosteen rind extract can inhibit and bactericide the growth of A. actinomycetemcomitans.